7y+2(y-9)=3(y+1)-2

Simple and best practice solution for 7y+2(y-9)=3(y+1)-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7y+2(y-9)=3(y+1)-2 equation:


Simplifying
7y + 2(y + -9) = 3(y + 1) + -2

Reorder the terms:
7y + 2(-9 + y) = 3(y + 1) + -2
7y + (-9 * 2 + y * 2) = 3(y + 1) + -2
7y + (-18 + 2y) = 3(y + 1) + -2

Reorder the terms:
-18 + 7y + 2y = 3(y + 1) + -2

Combine like terms: 7y + 2y = 9y
-18 + 9y = 3(y + 1) + -2

Reorder the terms:
-18 + 9y = 3(1 + y) + -2
-18 + 9y = (1 * 3 + y * 3) + -2
-18 + 9y = (3 + 3y) + -2

Reorder the terms:
-18 + 9y = 3 + -2 + 3y

Combine like terms: 3 + -2 = 1
-18 + 9y = 1 + 3y

Solving
-18 + 9y = 1 + 3y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-3y' to each side of the equation.
-18 + 9y + -3y = 1 + 3y + -3y

Combine like terms: 9y + -3y = 6y
-18 + 6y = 1 + 3y + -3y

Combine like terms: 3y + -3y = 0
-18 + 6y = 1 + 0
-18 + 6y = 1

Add '18' to each side of the equation.
-18 + 18 + 6y = 1 + 18

Combine like terms: -18 + 18 = 0
0 + 6y = 1 + 18
6y = 1 + 18

Combine like terms: 1 + 18 = 19
6y = 19

Divide each side by '6'.
y = 3.166666667

Simplifying
y = 3.166666667

See similar equations:

| 5/10y-36=0 | | (x-5y)(x+5y)= | | 5y^(8/3)+7y^(5/3)-6y^(2/3)=0 | | 8/9-3/7 | | 6/12y+65=0 | | -5/7(-7) | | (3x-4)*2-(x-7)*2=8x(x-2) | | 3/5(4) | | -8/9(5) | | -56+21= | | 6x+6x=90-x | | (4x+3)2+5(4x+3)-6=0 | | N/9+3=7 | | C+6=7+14 | | 7x-4=x+4 | | 5t+3t-1=7 | | 23-x=32-4x | | 8y+2(y-5)=3(y+1)-2 | | -4x(3x-5)= | | 9x+4=x+6 | | 2x-3y=78 | | 0.12(y-2)+0.20y=0.14y-1.5 | | 3/4-14=-8 | | 7(2x+5)= | | 4=-3u-(-7)/8 | | -1/2x+10=16 | | by=x+a | | 4(6+3h)=40 | | 2x-8=2x-6 | | -3d=-2 | | 5-5=3*-3 | | 2x+8(x-3)=4x+5(x-9) |

Equations solver categories